PERBEDAAN KETERAMPILAN MOTORIK HALUS ANAKUSIA 5-6 TAHUN MELALUI KEGIATAN MENJAHIT POLADI TK AISYIYAH BUSTANUL ATHFAL 01 MEDANT.A 2025 - Fepriana Asiska; Wan Nova Listia (CV. Adiba Aisha Amira, 2025)
This study aims to determine the differences in fine motor skills of children aged 5-6 years through pattern sewing activities at Tk Aisyiyah Bustanul Athfal 01 Medan. This type of research is a quantitative experiment with Pre-experimental design type one group pretest-posttest design. The sample in this study amounted to 17 children of group B at Tk Aisyiyah Bustanul Athfal 01. Data collection instruments include observation and documentation guidelines. Pattern sewing activities use flannel, plastic needles, wool thread as learning media. The results of the analysis show a significant change in children's fine motor skills after being treated. This is shown through the Wilcoxon test which obtained a significance value of 000 <0.05 so that H0 is rejected and Ha is accepted. Thus, pattern sewing activities using flannel are proven to have an effect on children's fine motor skills.